2012
DOI: 10.1152/ajprenal.00338.2011
|View full text |Cite
|
Sign up to set email alerts
|

A novel U-STAT3-dependent mechanism mediates the deleterious effects of chronic nicotine exposure on renal injury

Abstract: Previous data from our group have demonstrated (Arany I, Grifoni S, Clark JS, Csongradi, Maric C, Juncos LA. Am J Physiol Renal Physiol 301: F125-F133, 2011) that chronic nicotine (NIC) exposure exacerbates acute renal ischemic injury (AKI) in mice that could increase the risk for development and progression of chronic kidney disease (CKD). It has been shown that proximal tubules of the kidney can acquire characteristics that may compromise structural recovery and favor development of inflammation and fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…In addition, the reactive oxygen species produced in response to nicotine also induces mesangial cell proliferation and extracellular matrix deposition through pathways that involve increased expression of cyclooxygenase 2-derived prostaglandins and increased phosphorylation of extracellular signal-regulated protein kinases 1 and 2, c-Jun N-terminal kinases, activator protein 1, and protein kinase B. 195,196,204,[206][207][208][209][210] This aberrant proliferation and deposition mirrors the protein kinase C dependent processes by which hyperglycemia constricts glomerular arterioles to limit blood flow and, hence, oxygen delivery to the kidney. In an additional mirror of hyperglycemia, nicotine also promotes hypoxia by facilitating oxygen-consuming inflammation.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the reactive oxygen species produced in response to nicotine also induces mesangial cell proliferation and extracellular matrix deposition through pathways that involve increased expression of cyclooxygenase 2-derived prostaglandins and increased phosphorylation of extracellular signal-regulated protein kinases 1 and 2, c-Jun N-terminal kinases, activator protein 1, and protein kinase B. 195,196,204,[206][207][208][209][210] This aberrant proliferation and deposition mirrors the protein kinase C dependent processes by which hyperglycemia constricts glomerular arterioles to limit blood flow and, hence, oxygen delivery to the kidney. In an additional mirror of hyperglycemia, nicotine also promotes hypoxia by facilitating oxygen-consuming inflammation.…”
Section: Hypertensionmentioning
confidence: 99%
“…This occurs through increased expression of unphosphorylated signal transducer and activator of transcription 3 that induces renal proximal tubule cells to secrete the pro-inflammatory cytokine transforming growth factor β1 and the proinflammatory chemokine monocyte chemotactic protein 1. 210 Finally, with a higher daily number of cigarettes smoked or a longer duration of smoking the risk of developing hypertension increases. [211][212][213] Consequently, it is logical to assume that beyond its own specific mechanisms of inducing hypoxiamediated CDK, cigarette smoking also utilizes those manifest in hypertension.…”
Section: Hypertensionmentioning
confidence: 99%
“…An in vivo study, by ROOMANS et al [28], reported that nicotine alters the homeostasis of epithelial cells in the lung, enhances inflammatory reactions and increases eosinophil numbers in the trachea. In the mouse kidney, nicotine increases the production of TGF-β and the expression of epithelial-mesenchymal transition markers [29]. While in human hepatic cells it also induces TGF-β and collagen expression, promoting fibrogenesis [30].…”
Section: Nicotinementioning
confidence: 99%
“…Nicotine has toxic effects in the mesangial cells and proximal tubules of the kidney and causes renal damage (9,10). Nicotine also stimulates expression of markers of epithelialmesenchymal transition, such as vimentin, fibronectin, and α-smooth muscle actin in the renal epithelium (9,10).…”
mentioning
confidence: 99%
“…Nicotine also stimulates expression of markers of epithelialmesenchymal transition, such as vimentin, fibronectin, and α-smooth muscle actin in the renal epithelium (9,10). Because nicotine easily crosses the placenta, entering fetal blood, and is distributed in breast milk, the fetal and neonatal rats would be expected to receive nicotine via the placenta and mother's milk (11,12).…”
mentioning
confidence: 99%